Twelve prophets - Peter C. Craigie (United States of America, 1985)
The author of Twelve Prophets, Volume 2 completes his study with a commentary on Micah, a contemporary of Isaiah, who foretold the birth of the Messiah
Keywords: Bible -- Minor Prophets